Nonzero-sum Games as Distributed Games. (June 2014) - Rao, K.S. Mallikarjuna
In this expository article we introduce distributed games studied in Anantharam and Borkar (2007). We show that any nonzero-sum games can be seen as distributed games and draw the relation between the question of common information and the existence of Nash and correlated equilibria.